2018
DOI: 10.1213/ane.0000000000003841
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Postoperative Brain Health

Abstract: As part of the American Society of Anesthesiology Brain Health Initiative goal of improving perioperative brain health for older patients, over 30 experts met at the fifth International Perioperative Neurotoxicity Workshop in San Francisco, CA, in May 2016, to discuss best practices for optimizing perioperative brain health in older adults (ie, >65 years of age). The objective of this workshop was to discuss and develop consensus solutions to improve patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
141
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 79 publications
0
141
0
2
Order By: Relevance
“…Furthermore, the mean age of the study population was 63.9 and 66.9 in the GA and spinal groups, respectively, and patients with pre-existing cognitive dysfunction were excluded from the study, which limits generalizability of the findings to individuals of advanced age and individuals with dementia. Indeed, the practice guidelines for perioperative brain health published in 2018 concluded that, based on current available data, there is insufficient evidence to recommend the use of regional anesthesia instead of general anesthesia [23].…”
Section: Main Bodymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the mean age of the study population was 63.9 and 66.9 in the GA and spinal groups, respectively, and patients with pre-existing cognitive dysfunction were excluded from the study, which limits generalizability of the findings to individuals of advanced age and individuals with dementia. Indeed, the practice guidelines for perioperative brain health published in 2018 concluded that, based on current available data, there is insufficient evidence to recommend the use of regional anesthesia instead of general anesthesia [23].…”
Section: Main Bodymentioning
confidence: 99%
“…Although there is a need for further research and additional data to guide perioperative management of elderly individuals, recommendations have been developed based on current evidence [23]. The fifth international perioperative neurotoxicity working groups included over 30 experts who developed recommendations specific to postoperative brain health in individuals > 65 years of age.…”
Section: Main Bodymentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Of note, postoperative cognitive dysfunction (POCD) is a significant complication after surgery that impairs learning, memory, and other cognitive functions. 3,4 POCD occurs days to weeks after surgery and could become a persistent disorder, being associated with an increased mortality within the first 3 months post-surgery. 5 Hence, strategies to better prevent and control the development of POCD are urgently needed.…”
Section: Introductionmentioning
confidence: 99%